Cartel stability in experimental auctions - Jeroen Hinloopen; Sander Onderstal; Leonard Treuren (Tinbergen Institute, 2019)
Using laboratory experiments, we compare the stability of bidding rings in the English auction and the first-price sealed-bid auction in a heterogeneous-value setting. In both a re-matching condition and a fixed-matching condition, we observe that biddings rings are more stable in the English auction than in the first-price sealed-bid auction. In both conditions, the first-price sealed-bid auction dominates the English auction in terms of average revenue and the revenue spread. The English auction outperforms the first-price sealed-bid auction in terms of efficiency.
Keywords: C92; D44; L41; 330; Cartel stability; English auction; First-price sealed-bid auction; Laboratory experiments